Tunnelling for the third section of the Stadtbahn line U12 in Stuttgart / Der Vortrieb für den dritten Teilabschnitt der Stadtbahnline U12 in Stuttgart. Issue 5 (October 2014) - Gradnik, Richard; Kicherer, Manfred; Zwick, Markus
Abstract Under contract to SSB, the urban rail operator in Stuttgart, Alfred Kunz Untertagebau München has been working on the Waltraud Tunnel since February 2014, which is the key structure in the extension of the U12 in the third section from Hallschlag to the Aubrücke bridge. This tunnel, with a length of 200 m, is mostly being constructed in fill material. The greatest challenge will be to tunnel beneath a 150 year old railway embankment with less than one diameter cover under continued operation. In order to minimise settlement and to reduce risk for the client, it is planned to drive the tunnel with two side headings. Alternatively to the tendered concept of a side heading drive, an optimisation of construction operations was investigated as part of the detailed design, which differed from the tendered tunnelling concept in investigating full face excavation for comparison with the tender variant. Im Auftrag der Stuttgarter Straßenbahnen AG errichtet Alfred Kunz Untertagebau München ab Februar 2014 den Waltraudtunnel, der das Herz der Erweiterung der U12 im dritten Teilabschnitt vom Hallschlag zur Aubrücke ist. Dieser Tunnel mit einer Länge von 200 m wird großteils in Auffüllungsmaterial errichtet. Als Höhepunkt wird ein ca. 150 Jahre alter Bahndamm mit weniger als einem Durchmesser Überlagerung unter laufendem Betrieb durchfahren. Zur Setzungsminimierung und zur Minimierung der Risiken für den Auftraggeber ist es geplant, den Tunnel mit doppelten Ulmenstollen aufzufahren. Alternativ zum ausgeschriebenen Konzept eines Ulmenstollenvortriebs wird im Zuge der Ausführungsplanung eine baubetriebliche Optimierung untersucht, die abweichend vom ausgeschriebenen Vortriebskonzept die Durchörterung im Vollausbruch untersucht und mit der ausgeschriebenen Variante vergleicht.